Motivasi Intrinsik, Pola Asuh Orangtua Demokratis dan Kreativitas Anak Sekolah Dasar - Gunawan, Lindawati; Farid, Muhammad (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2014)
Abstrak. This study aims to determine the relationship between intrinsic motivation and democratic parenting parents to elementary school children's creativity. Subject of this study is Fifth grade students of Petra 5 Christian Elementary School to 90 students. The results showedthatthere wasa significant correlation between intrinsic motivation and democratic parenting parents to creativity (F = 4.081top=0.023); partially obtained results indicate that intrinsic motivation correlated significant positive towards creativity(t =2.334top=0.024), while between democratic parental parenting variables and creativity did not show anycorrelation(t =0.774top=0.443).Keywords: intrinsic motivation, democratic parenting parents, and creativity.